2014
DOI: 10.1074/jbc.m114.558825
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-relevant Splicing Factor CAPERα Engages the Essential Splicing Factor SF3b155 in a Specific Ternary Complex

Abstract: Background: CAPER␣ contains a U2AF homology motif (UHM) that typically recognizes U2AF ligand motifs (ULM) of pre-mRNA splicing factors. Results: Crystal structures reveal CAPER␣ UHM/SF3b155 ULM interactions. CAPER␣ preferentially associates with the SF3b155 ULM-containing domain. Conclusion: CAPER␣ is recruited for pre-mRNA splicing via UHM/ULM interactions with SF3b155. Significance: Knowledge of CAPER␣/SF3b155 complexes will enhance understanding of angiogenic spliceoform regulation by CAPER␣.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(93 citation statements)
references
References 56 publications
6
87
0
Order By: Relevance
“…2E,F; (Thickman et al 2006). Consistent with findings for the U2AF 65 UHM, a battery of methods including size exclusion chromatography, amino acid analysis, and ITC show that two CAPERα UHMs concurrently bind the SF3b155 ULMcontaining region under saturating conditions (Loerch et al 2014). The Hill coefficient of pull-downs from human cell extract further suggests that endogenous, full length CAPERα binds a GST-fused ULM-containing region of SF3b155 with positive cooperativity (Loerch et al 2014).…”
Section: Potential Functions Of Multiple Functions Of Multiple Sf3b15mentioning
confidence: 50%
See 4 more Smart Citations
“…2E,F; (Thickman et al 2006). Consistent with findings for the U2AF 65 UHM, a battery of methods including size exclusion chromatography, amino acid analysis, and ITC show that two CAPERα UHMs concurrently bind the SF3b155 ULMcontaining region under saturating conditions (Loerch et al 2014). The Hill coefficient of pull-downs from human cell extract further suggests that endogenous, full length CAPERα binds a GST-fused ULM-containing region of SF3b155 with positive cooperativity (Loerch et al 2014).…”
Section: Potential Functions Of Multiple Functions Of Multiple Sf3b15mentioning
confidence: 50%
“…Alternatively, the SF1 ULM is recognized by the UHM of the KIS/UHMK1, which directs phosphorylation of an SF1 SPSP motif (Manceau et al 2006(Manceau et al , 2008. Soon thereafter, we and others noticed seven ULM-like repeats in the Nterminal region of the SF3b155 subunit of the U2 snRNP, and confirmed that five of these putative SF3b155 ULMs detectably associate with UHMs (Thickman et al 2006;Corsini et al 2007Corsini et al , 2009Loerch et al 2014). The SF3b155 ULM-U2AF 65 UHM complex is likely to assist SF1 displacement and stable association of the U2 snRNP during spliceosome assembly, whereas other UHM-containing splicing factors may regulate this process.…”
Section: A Limited Cohort Of Established "U2af Ligand Motifs"mentioning
confidence: 51%
See 3 more Smart Citations